2022
DOI: 10.3390/su142113986
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Physical Activity and Depressive Symptoms in Middle-Aged and Elderly People Controlling for Demographic and Health Status Variables

Abstract: Objective: To explore the relationship between physical activity intensity and depressive symptoms in Chinese middle-aged and elderly people, and to provide new evidence for the prevention and treatment of depression by physical activity. Methods: The data came from the 2018 China Health and Retirement Longitudinal Study. Using the PPS sampling method, a baseline survey was conducted among middle-aged and elderly people over the age of 45 across the country to investigate their demographics, health status, eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(30 reference statements)
1
6
0
1
Order By: Relevance
“…This study found that older people have a higher risk of depressive symptoms. This result is consistent with the results of Zhang Y et al [21] They found that PA level of middle-aged and elderly decreases with age, but the risk of depression also increases. They suggested that more attention should be paid to the effect of aging on mental health of older people.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study found that older people have a higher risk of depressive symptoms. This result is consistent with the results of Zhang Y et al [21] They found that PA level of middle-aged and elderly decreases with age, but the risk of depression also increases. They suggested that more attention should be paid to the effect of aging on mental health of older people.…”
Section: Discussionsupporting
confidence: 93%
“…Demographic, health status, and lifestyle variables. Demographic variables include gender (male or female), age (50-59 or 60-69 or 70-79 or 80-89 or 90 and above), [21] type of household registration (urban or rural), education level (below high school or above high school), and widowhood (yes or no). Health status and lifestyle variables include hypertension (yes or no), hyperlipidemia (yes or no), diabetes (DM) (yes or no), stroke (yes or no), asthma (yes or no), arthritis (yes or no), bad mood (yes or no), physical activity (PA) level (high or low), and smoking (yes or no).…”
Section: Variablesmentioning
confidence: 99%
“…For older people with diseases, intergenerational contact also has a positive impact. Frequent family intergenerational contact has been found to improve self-rated health in older adults by alleviating depression [38] . In terms of work, the influence of contact between the elderly and young people on work engagement, and the attitudes of middle-aged and older workers play a partial mediating role [39] .…”
Section: Intervention Measuresmentioning
confidence: 99%
“…[8,9] Insufficient physical activity has been shown to be associated with increased risk of weight gain, metabolic syndrome, diabetes, and heart disease. [10] Therefore, there is a chance that college students would develop chronic illnesses in the future, which will be expensive for the family and society. [11][12][13] College students mental health issues are particularly severe due to their changing living conditions and mounting academic pressure, and they are becoming a major global public health concern.…”
Section: Introductionmentioning
confidence: 99%